RESULTS OF LEARNING SCIENCE CLASS 3 WITH DISCUSSION METHOD HELPED MEDIA GREAT IMAGES - Izzaturrahmah Izzaturrahmah; Ahmad Harjono; Moh. Irawan Zain (PROGRES PENDIDIKAN, 2022)
This research is aim to know the effect of discussion method by using serial image media toward study result of science class III cluster III subdistrict of Sekarbela lesson year 2019/2020. This research using Quasi Experiental Design type Nonequivalent Control Group Design. The sample ethnic that used is Purposive Sampling, one of the researcher opinion of using this sample type because the average of study result of science students are same, that was taken from placement test. Total of this sample are 58 students. Students result data tested is normalization using kolmogorov smirnov formula said that it has normal distribution then later tested homogenitation using levene statistic formula said it has varian homogen by using SPSS 21 for windows, at the end the tested shows that the data has normal distribution and tested homogen. Then tested hypothesis using independent sample t-test formula got t-hitung 1,013 as bis as and t-table as big as 3,172 with standart of significant are 5%. The explanation above show that t-hitung > t-table so it can conclude that Haaccepted and H0rejected. This case shows that there is effect of discussion method by using serial image media toward study result of science class III cluster III subdistrict of Sekarbela lesson year 2019/2020.